Pengaruh konsumsi kopi terhadap kebiasaan begadang dan kualitas tidur mahasiswa: Tinjauan literatur - Setyawan, Ardi Dwi (Maliki Interdisciplinary Journal, 2025)
Increased coffee consumption among university students is a phenomenon that is closely related to academic pressure, the culture of staying up late, and high productivity demands. Coffee is used as a quick solution to improve focus and resist sleepiness, especially when facing assignments and exams. This article aims to theoretically review the effect of coffee consumption on college students' staying up late habits and sleep quality. This review is conducted through a literature study that covers the pharmacological theory of caffeine, physiological mechanisms of the sleep system, as well as studies related to coffee consumption among university students. The review showed that caffeine in coffee works as an adenosine receptor antagonist that disrupts circadian rhythms and natural sleep-wake mechanisms. Excessive caffeine consumption especially at night has the potential to cause sleep disturbances, insomnia, daytime fatigue, and decreased concentration. On the other hand, coffee consumption is also reinforced by psychological aspects and campus culture that normalizes staying up late as a form of academic dedication. This study emphasizes the importance of educating wise caffeine consumption and promoting a healthy academic lifestyle to maintain a balance between productivity and health.